Model Transformasi SDM Berbasis Pendekatan Lintas Disiplin dalam Mendorong Pemberdayaan Masyarakat Berkelanjutan di Era Digital - Arief Fahmi Lubis; Tri Agus Suswantoro (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This community service activity aims to explore strategies for strengthening human competencies in facing technological disruption through a national seminar entitled “Human Resource Transformation in the Digital Era: An Interdisciplinary Approach for Sustainable Community Empowerment.” The seminar featured expert speakers from various universities to provide multidimensional perspectives for participants. The discussion focused on the integration of digital technology, adaptation of organizational culture, and management innovation to enhance community economic resilience. The implementation method involved intensive material presentations and interactive discussions that bridged academic theory with practical field needs. The results of the activity indicated an increase in participants’ awareness and understanding of the importance of digital literacy and interdisciplinary collaboration as key factors for inclusive empowerment. Through synergy among academics, the seminar successfully formulated strategic recommendations for developing adaptive, innovative, and globally competitive human resources. It is expected that the outcomes of this activity will serve as a catalyst for achieving sustainable community independence amid the rapidly evolving digital ecosystem. Recognizing the importance of this issue, the seminar was held on March 7, 2026, and comprehensively discussed strategies, insights, and research findings related to human resource transformation in the digital era, including how organizations can become more competitive.